Dynamics of symbiotic bacterial community in whole life stage of Harmonia axyridis (Coleoptera: Coccinellidae) - Du, Lingen; Xue, Hui; Hu, Fangmei; Zhu, Xiangzhen; Wang, Li; Zhang, Kaixin; Li, Dongyang; Ji, Jichao; Niu, Lin; Luo, Junyu; Cui, Jinjie; Gao, Xueke (Frontiers in Microbiology, 2022)
Bacteria play critical roles in the reproduction, metabolism, physiology, and detoxification of their insect hosts. The ladybird beetle (Harmonia axyridis) harbors a myriad of endosymbiotic microbes. However, to date, little is known about how the microbial composition of H. axyridis varies throughout its life cycle. In this study, 16S rRNA amplicon sequencing and quantitative PCR were employed to investigate the diversity and dynamics of bacterial symbionts across the egg, larval, pupae, and adults stages of H. axyridis. Higher bacterial community richness and diversity were observed in eggs, followed by those in adults and pupae. The community richness index differed significantly between second instar larvae and other developmental stages. Proteobacteria, Firmicutes, and Actinobacteria were the dominant phyla. Staphylococcus, Enterobacter, Gluamicibacter, and Acinetobacter were the dominant bacteria genera, however their relative abundances fluctuated across host developmental stages. Interestingly, the larval stage harbored high proportions of Firmicutes, whereas the adult microbial community largely consisted of Proteobacteria. This study is the first to determine the symbiotic bacterial composition across key life stages of H. axyridis. These outcomes can foster the development of environmental risk assessments and novel biological control strategies.